Changes in facial signs due to age and their respective weights on the perception of age and skin plumpness among differently aged Korean women. Issue 4 (9th November 2020) - Flament, Frederic; Prunel, Anne; Keufer, Benjamin; Abric, Aurelie; Wang, Yang; Reni, Alexandra; Cassier, Matthieu; Delaunay, Caroline
Abstract: Objective: To determine the respective weights of certain facial signs on the assessment of perceived age and plumpness on Korean women of different ages. Material and Methods: Photographs were taken of the faces of 112 Korean women of different ages (18‐80 years) under standardized conditions. These photographs allowed to focus and define 19 facial signs, which were then graded by 15 experts and dermatologists, using standardized scales provided by a reference Skin Aging Atlas. The facial signs were dispatched into 5 clusters, namely Wrinkles/Texture, Ptosis/Sagging, Pigmentation disorders, Vascular disorders, and Cheek skin pores. A naïve panel, composed of 92 Korean women, of similar age range were asked, when viewing full‐face photographs, to: (a) attribute on a 0‐10 scale their perception of the skin plumpness (ie supple/hydrated/nourished) and (b) estimate the age of the subject. Results: With the exception of Vascular disorders, the severity of all 4 clusters increased with age, although at different rates. The Wrinkles/Texture or Ptosis/Sagging showed a rather regular progression. Although perceived ages and real ages were found highly correlated, half of the subjects were judged older by 2‐12 years. The facial signs/clusters were significantly correlated with perceived age, with the exceptions of vascular disorders, size of pigmentary spots and cheek skin pores. The weights in perceived ages of Wrinkles/Texture and Ptosis/Sagging represent 37% each and Pigmentation disorders at 26%. Skin plumpness was logically found significantly anti‐correlated with perceived age. If, surprisingly, Vascular disorders were found not impacting the plumpness aspect, Cheek skin pores presented a clear influence. Conclusion: Within facial clinical clusters, Wrinkles/Texture, Ptosis/Sagging, and Pigmentation disorders are major factors in the assessment of perceived age in Korean women. The perception of a decreased skin plumpness is significantly associated with increased perceived age.